Prioritizing hazardous pollutants in two Nigerian water supply schemes: a risk-based approach - Ayotunde T Etchie; Tunde O Etchie; Gregory O Adewuyi; Kannan Krishnamurthi; S Saravana Devi; Satish R Wate (Bulletin of the World Health Organization, 2013)
Abstract Objective To rank pollutants in two Nigerian water supply schemes according to their effect on human health using a risk-based approach. Methods Hazardous pollutants in drinking-water in the study area were identified from a literature search and selected pollutants were monitored from April 2010 to December 2011 in catchments, treatment works and consumer taps. The disease burden due to each pollutant was estimated in disability-adjusted life years (DALYs) using data on the pollutant's concentration, exposure to the pollutant, the severity of its health effects and the consumer population. Findings The pollutants identified were microbial organisms, cadmium, cobalt, chromium, copper, iron, manganese, nickel, lead and zinc. All were detected in the catchments but only cadmium, cobalt, chromium, manganese and lead exceeded World Health Organization (WHO) guideline values after water treatment. Post-treatment contamination was observed. The estimated disease burden was greatest for chromium in both schemes, followed in decreasing order by cadmium, lead, manganese and cobalt. The total disease burden of all pollutants in the two schemes was 46 000 and 9500 DALYs per year or 0.14 and 0.088 DALYs per person per year, respectively, much higher than the WHO reference level of 1 × 10−6 DALYs per person per year. For each metal, the disease burden exceeded the reference level and was comparable with that due to microbial contamination reported elsewhere in Africa. Conclusion The estimated disease burden of metal contamination of two Nigerian water supply systems was high. It could best be reduced by protection of water catchment and pretreatment by electrocoagulation.